Oxford international lower secondary english student book 2 For grade 7 - Barber, Alison; Redford, Rachel (Karachi: Oxford university press, 2023)
This edition of Oxford International Lower Secondary English gives students the skills they need to become confident communicators with a strong grasp of English language, vocabulary and grammar. Students discover the joy of learning through speaking and listening, reading extracts from around the world, writing and performing.
Keywords: Oxford English